SAT0201 Treatment Adherence in Rheumatoid Arthritis (RA) Patients Followed in a Specific Biological Therapy Unit. a Pilot Study. (9th June 2015) - Mena-Vazquez, N.; Manrique-Arija, S.; Yunquera, L.; Ureña-Garnica, I.; Cano-García, L.; Ordoñez-Cañizares, M.C.; Domic, C.; Rojas-Giménez, M.; Fuego, C.; Jiménez Núñez, F.G.; Romero-Barco, C.M.; Irigoyen-Oyarzábal, M.V.; et al.
Abstract : Objectives: To study the adherence to biologic therapy (BT) of patients with RA. Methods: Design: Cross-sectional study. Patients: 40 RA-pts treated with BT (50% wit subcutaneously [sc] and 50% with intravenously [iv]) with or without synthetic DMARDs were consecutively recruited from a specific unit of BT. Protocol: Patients with sc BT are alternately reviewed every three months in general and specific (only BT pts) outpatient clinic. Iv BT patients are checked each time the drug is infused. At 5 days from 1st iv BT infusion or in the day that 2nd dose of sc BT is given, patients receive a call from the nurse to confirm that everything went well. Patients with sc BT have a self-injections diary and direct free telephone access to the nurse. Variables: Demographic, clinical and laboratory, therapeutic, Morisky-Green adherence questionnaire (MGAQ), control of the number of sc BT doses withdrawn from outpatient hospital pharmacy, assisting to infusions in the case of iv BT and removal of synthetic DMARDs in the drugstores using "XXI electronic prescription" (a software used to control the dispensations in the public health system in Andalusia) in the last 6 months. Outcome variables: (1) level of adherence and (2) compliance level with MGAQ. MGAQ considers that the patients are adherents when they give 3 or more responses indicative of adherence. Good drug withdrawal from hospital pharmacy or drugstore was defined as removal of >80% of the prescribed dose. Adherence to BT and synthetic DMARDs was measured independently. The degree of adhesion was classified as good (3 or 4 correct responses in MGAQ and good drug withdrawal), medium (3 or 4 good responses in MGAQ but bad drug withdrawal or vice versa) and bad (<3 good responses in MGAQ and bud drug withdrawal). Statistical analysis: Descriptive analysis of the main variables. Adherence between sc BT and iv BT was compared using T-Student. Results: The main characteristics of the patients (n=40) are shown in the table . 10/40 patients were in monotherapy. 37/40 (92.5%) showed good adherence to BT, 3/40 (7.5%) moderate and bad none. There was no difference in the level of adherence to BT among sc BT and iv. BT (90% vs. 95% good adhesion; p=0.50) nor between BT alone or in combination with DMARDs (70% vs. 100% good adhesion; p=0.12). The level of adherence was good with BT in 100% of the patients and in the 70% with synthetic DMARDs. Conclusions: Adherence to BT in RA-patients in a specific unit of BT that controls the treatment adherence is very good with the BT and good with synthetic DMARDs. Patients treated with sc or iv. BT and those with monotherapy or combination therapy are equally adherents. These data represent are only a preliminary study. Disclosure of Interest: None declared